A new freshwater gobiid species of Rhinogobius Gill, 1859 (Teleostei: Gobiidae) from Minjiang river basin, Fujian Province, southeastern China - Chen, I-Shiung; Wei, Yu-Chun (Zootaxa, 2024)
A new freshwater gobies of Rhinogobius Gill, 1859 were discovered from the Minjiang Basin, Fujian Province, southeastern China. It belongs to fluvial species. The new species, Rhinogobius dongfongensis n. sp. which collected from Fujian Province of China can be well distinguished from all other congeners by the unique combination of the following features: (1) fins: second dorsal fin rays modally I/8–9; anal fin rays I/7; pectoral fin rays modally 15; (2) squamation: longitudinal scale series 32–33 (modally 33); perdorsal scales usually 5–6; (3) normal vertebral count 26; (4) rear edge of mouth merely extending beyond vertical of anterior margin of pupil in male and (5) its own specific colouration. The brief comparison and discussion of morphological differentiation from congeners of mainland China would be addressed.